Isolasi dan Identifikasi Struktur Karotenoid dari Ekstrak Bayam Merah (Amaranthus Tricolor L.) - Sulistyaningrum, Novi (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2014)
Amaranthus tricolor L. was reported as source of carotenoid compounds (tetraterpenoids) which is a natural pigments and has bioactivity as antioxidants. They are beneficial to health. Carotenoids isolate are obtained by maceration method in methanol, saponification with KOH / MeOH 5%, fractionated by vacuum column chromatography, preparative thin layer chromatography (preparative-TLC) repeatedly and each fraction monitored using thin layer chromatography (TLC). Structure analysis of carotenoids based on UV, IR and GCMS spectroscopic data showed similarities as lutein structure.